Establishing the effect of low-percentage doses of foaming agents on increasing fluid consumption at its transportation by fire hoses - Stas, Serhiy; Kolesnikov, Denis; Bychenko, Artem; Borsuk, Olena (Eastern-European Journal of Enterprise Technologies, 2025)
In the cases where there is a need to quickly move large volumes of water over a distance of hundreds of meters, firefighting equipment is used. In such cases, hose lines formed from fire hoses are usually used. An attempt was made to determine the effect of microdoses of foaming agents on the level of fluid consumption transported by fire hoses. It has been experimentally established that the fluid consumption during its transportation by fire hoses increased when foaming agents were added to it. The foaming agents Pirena-1, Sofir, Alpen, and Bars, which are used in firefighting in Ukraine, were selected for the experiments. Each of the foaming agents was used in two versions – one that meets and one that does not meet the guaranteed shelf life. The maximum increase in flow rate (11.5 %) was recorded when adding 0.021 % of the Bars foaming agent to water. The results of the experiments depended on the brand of foaming agents used and were almost independent of the “age” of the foaming agents. It is important that the results of the study showed that “overdue” foaming agents can be used to increase the efficiency of fire-fighting equipment. Latex-coated pressure fire hoses with a diameter of 51 mm were randomly selected (from those available in the fire department). The length of the hose line was 200 m (500 m for hoses with a diameter of 77 mm), the ambient temperature was about 20 °C, the pressure at the pump was 4…6 bar. The facts of the increase in liquid flow rate established in the study could be used in practice to increase the amount of liquid transportation (pumping) without changing other parameters of the fire-fighting equipment, for example, when eliminating the consequences of floods or landslides